Poverty Measurement In Malaysian Zakat Institutions: A Comparison Between Monetary And Non-Moneary Measurement - Mohamed Saladin Abdul Rasool; Ariffin Md Salleh (Media Syari'ah, 2017)
There are various definitions of poverty in the teachings of Islam. In principle the poor are defined as those whose needs are insufficient. Thus, Islamic institutions in Malaysia play a variety of socioeconomic roles such as poverty alleviation. To perform this role, these institutions face a major task in identifying the poverty group. Most of these institutions measure and operationalize poverty from the monetary perspective using variables such as income, expenditure or consumption. In practice, most Islamic institutions in Malaysia use the monetary approach in measuring poverty through the conventional Poverty Line Income (PLI) method and also the Islamic based Had Al-Kifayah (HAK) method. The objective of the paper is to present a non-monetary shariah based poverty measurement, Islamic Poverty Index (IPI), consisting of maqasid-al sharia (objective of the religion) elements, namely religion, knowledge, physical-self, offspring and wealth. The IPI, calculated using the weighted index method is expected to exemplify poverty from a multidimensional perspective. In addition, a comparison with the HAK method was highlighted. A survey aided by a structured questionnaire using expert review was carried out on 258 selected head of households in the state of Selangor, the most populated state in Malaysia. Poverty groups identified from each of the methods were highlighted using descriptive statistics. In addition, regression analysis revealed that unemployment was the common significant determinant of poverty according to both the IPI and HAK method.